Using Android-Based E-Module to Improve Students’ Digital Literacy on Chemical Bonding - Dewi, Citra Ayu; Awaliyah , Nurdianti; Fitriana , Nurin; Darmayani , Satya; Nasrullah; Setiawan , Jan; Irwanto, Irwanto (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Digital literacy is critical in the current era of digitalization. Therefore, students are required to be digitally literate. This study aims to improve students’ digital literacy using an android-based e-module in chemical bonding. This study used a quasi-experimental method with a pre-experimental design that included a pretest and posttest for one group. For this study, 70 preservice teachers (10 males and 60 females) from the Department of Chemistry Education at a private university in Indonesia were recruited. The Digital Literacy Questionnaire (DLQ) was used to measure students’ digital literacy. To analyze the data, we used paired t-tests and N-gain. The results indicated a significant increase in digital literacy scores before and after treatment. Thus, it can be concluded that using an android-based e-module significantly enhances students’ digital literacy on chemical bonds. Due to its effectiveness, we recommend teachers use this e-module to elevate students’ academic performance, in general, in chemistry.